Model Pembelajaran Bahasa dan Sastra Berbasis Kearifan Lokal Makassar - Dedi Gunawan Saputra (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to develop a language and literature learning model based on Makassar local wisdom at SMA Negeri 11 Makassar with a focus on strengthening students' character and identity. Through qualitative methodology, this research explores how Makassar's local cultural values can be integrated into teaching materials, so that students not only understand language and literature but also appreciate and preserve its cultural heritage. The data collection method is carried out through observation and recording, and data analysis is carried out with descriptive techniques. The results of the study show that the application of this learning model has a positive impact on students' understanding of Makassar's local culture, increasing their appreciation of traditional literary works and strengthening cultural identity. In addition, this model also contributes to creating a more contextual and relevant learning environment. The conclusion of this study is that the integration of Makassar local wisdom in language and literature learning is very important to shape the character and identity of students, as well as encourage the preservation of regional languages and literature among the younger generation.